2016
DOI: 10.1038/cddis.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoptosis-related miRNAs in resveratrol-induced breast cancer cell death

Abstract: Breast cancer is the most frequently diagnosed cancer in women, and one of the leading causes of cancer-related deaths worldwide. Recent evidences indicate that dietary agents such as resveratrol may inhibit cancer progression through modulation of microRNAs (miRNAs). We demonstrate that resveratrol regulates apoptotic and cell cycle machinery in breast cancer cells by modulating key tumor-suppressive miRNAs including miR-125b-5p, miR-200c-3p, miR-409-3p, miR-122-5p and miR-542-3p. Resveratrol-mediated miRNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(161 citation statements)
references
References 58 publications
6
149
0
Order By: Relevance
“…Interestingly, emerging studies have demonstrated that some herbal product (e.g curcumin, camptothecin, andrographolide and resveratrol etc.) can perform their anti-tumor effects through affecting miRNAs expression [16, 23-25]. However, whether the antitumor effect of baicalein is related to its modulation of miRNA expression in HCC is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, emerging studies have demonstrated that some herbal product (e.g curcumin, camptothecin, andrographolide and resveratrol etc.) can perform their anti-tumor effects through affecting miRNAs expression [16, 23-25]. However, whether the antitumor effect of baicalein is related to its modulation of miRNA expression in HCC is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that andrographolide could altered miRNA expression profile and its downstream signals in hepatoma tumor tissues from mice [24]. Additionally, another recent study showed that resveratrol could regulate apoptotic and cell cycle machinery in breast cancer cells by modulating key tumor-suppressive miRNAs including miR-125b-5p, miR-200c-3p, miR-409-3p, miR-122-5p and miR-542-3p [25]. However, there is still no related report about the effects of baicalein on miRNA expression profile when it exerts its inhibition on hepatoma tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its pleiotropic activity, resveratrol is able to suppress or to interfere with these key inflammatory molecular targets almost instantly [61]. In addition, recent interest in resveratrol has focused on its ability for modulation of tumor-suppressive miRNA by inducing apoptotic cell death [62,63]. In absence of a clear mechanistic link, the activity of resveratrol may be partially dependent upon an impaired expression of certain miRNAs associated with inflammatory and tumor suppression effects (miR-663), proinflammatory effects (miR-155), or oncogenicity (miR -21).…”
Section: Molecular Targets Of Resveratrolmentioning
confidence: 99%
“…[8][9][10] Res also has neuroprotective effects and improves the pathological and behavioral outcomes of various types of nerve injury, including stroke, 11 traumatic brain injury, 12 spinal cord injury, 13 and peripheral nerve injury. 14 A number of mechanisms have been proposed to explain Res-induced neuroprotection, many of which invoke its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%